Campaña de vacunación covid 19: Respuesta ciudadana y estrategia de comunicación de la alcaldía de Babahoyo 2021 - Contreras Zamora, Alexander Adrián (2022)
This academic paper focuses its analysis on the Covid 19 Vaccination Campaign: Citizen Response And Communication Strategy Of The Mayor's Office Of Babahoyo 2021, which allows identifying and confirming that, worldwide, the vaccines of arnm as pfizer and modern have been used to protect millions of people against covid-19, therefore, it is relevant that there are surveillance programs of countries on their efficacy and safety. (chauca, 2021). Vaccination is a simple, safe and effective way to protect us against harmful diseases before we come into contact with them. Vaccines activate the body's natural defenses so that it learns to resist specific infections, and strengthen the immune system. After vaccination, our immune system produces antibodies, as it does when we are exposed to a disease, with the difference that vaccines contain only killed or weakened microbes (such as viruses or bacteria) and do not cause disease or complications. (Trilla, 2020). Regarding the methodology, a descriptive study is developed, in which it is intended to identify the participation of citizens in the covid-19: vaccination campaign of the mayor's office of Babahoyo in 2021. The technique to be used in this case study is the digital survey to a maximum of 383 people, a sample of the total population of Babahoyo, which among the results reflected high rates of participation and acceptance.